Subsistence migration: Smallholder food security and the maintenance of agriculture through mobility in Nicaragua. Issue 2 (7th December 2018) - Carte, Lindsey; Radel, Claudia; Schmook, Birgit
Abstract : Research on Central American migration has revealed the importance of journeys to the global North for rural sending communities. The outcomes of south–south journeys to nearby countries are less explored, although they are commonplace. We examine Nicaraguan rural residents' migration to other Central American countries, especially El Salvador, to understand this migration's impacts on agricultural systems and food security. Based on mixed‐methods fieldwork in north‐western Nicaragua, we find that rather than produce remittance landscapes, or an abandonment of agriculture, south–south migration is linked to the maintenance of small‐scale agricultural systems and thus food production. "Subsistence migration, " or mobility to maintain small‐scale agriculture as a food security strategy, draws attention to how these less explored forms of migration in Central America help families to persist in agriculture in a context of worsening environmental and structural conditions. Abstract : This article examines Nicaraguan rural residents' migration to other Central American countries, especially El Salvador, and resulting impacts on agricultural systems and food security. Findings indicate that rather than produce remittance landscapes, or an abandonment of agriculture, "subsistence migration" is linked to the maintenance of small‐scale agricultural systems and thus food production.